Internet Access : Regulatory Levers for a Knowledge Economy - Mustafa, Mohammad A. (World Bank, Washington, DC, 2012)
Internet access depends on four critical players: First, providers of telecommunications infrastructure (bandwidth capacity) for international access to the global Internet backbone. Second, providers of national long-distance telecommunications transmission capacity (such as leased lines) to connect Internet service providers (ISPs) with one another and with international connectivity nodes. Third, providers of local loop access (narrowband and analogue, such as traditional copper wire connections, or broadband and digital, such as digital subscriber lines [DSL], cable television modems, and fixed wireless service). Fourth, ISPs, which provide Internet services to customers using these layers of networks. Expanding Internet access requires cooperative behavior by these players, and regulators have a key role in ensuring such behavior. A regulatory strategy for doing so focuses on promoting the telecommunications infrastructure, enabling viable ISPs, ensuring efficient pricing, maintaining appropriate service quality, supporting diffusion in remote areas, and ensuring legal certainty for electronic transactions. Promoting the telecommunications Infrastructure - competition is key. So regulators should take a permissive approach to licensing multiple financially sound providers (owners and resellers) of telecommunications infrastructure for international connectivity, alternative national long distance networks, and local loop access. To ensure competition in the ISP market, regulators should require no formal licensing for ISPs; simple registration should suffice.